2008
DOI: 10.1007/s11483-008-9097-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Crystallinity on the Physical Properties of Inulin during Water Sorption

Abstract: The impact of the crystallinity of spray-dried inulins on their stability and physical properties was investigated after a conditioning of 1 week at different relative humidity levels (0% to 94%) at 20°C. An environmental scanning electron microscopy study showed that the amorphous powders hardened at a relative humidity storage between 59% and 75%; while their semi-crystalline counterparts were partially agglomerated but friable in the same conditions. Caking was observed when the glass transition temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…The untreated raw powder (RP), supplied as a large batch of dry material, had a >60% content of AI-1 as revealed by both Tc (OD) and Tc (RI) (data not shown) and its MP of MP2. It also has a lower peak (MP1) commonly attributed to the MP of inulin organized through the plasticizing effect of water (Ronkart et al 2009(Ronkart et al , 2010. A plot of mean (dry) MP value against MP number (or isoform type) reveals a close linear relation ( Figure 9B) unlike the nonlinear relation seen for the (wet) Tc values.…”
Section: Reversibility Of Isoformsmentioning
confidence: 92%
“…The untreated raw powder (RP), supplied as a large batch of dry material, had a >60% content of AI-1 as revealed by both Tc (OD) and Tc (RI) (data not shown) and its MP of MP2. It also has a lower peak (MP1) commonly attributed to the MP of inulin organized through the plasticizing effect of water (Ronkart et al 2009(Ronkart et al , 2010. A plot of mean (dry) MP value against MP number (or isoform type) reveals a close linear relation ( Figure 9B) unlike the nonlinear relation seen for the (wet) Tc values.…”
Section: Reversibility Of Isoformsmentioning
confidence: 92%
“…The fats present in butter, margarine, or spreads mostly have melting temperatures below the temperature of the mouth cavity temperature (Rousseau & Marangoni 1998). The solubility temperature of the amorphous forms of commercial high performance inulin with the degree of polymerisation ≥ 23 is much higher than 36.6°C, thus the crystal forms of inulin present in the analysed samples are more difficult to dissolve (Kim et al 2001;Bot et al 2004;Ronkart et al 2009). The presence of inulin in the analysed samples caused a small but statistically insignificant (P ≤ 0.05) decrease For explanation I-Wp see Table 1 in margarine flavour.…”
Section: Resultsmentioning
confidence: 99%
“…The amorphous structure of the yacon saccharides powder may explain its high hygrospicity. A relatively large amount of works have reported the caking of amorphous products exposed to various water vapor pressures (Meste et al 2002;Ronkart et al 2006;Omar and Roos 2007;Ronkart et al 2009a, b). According to Hartmann and Palzer (2011) crystalline substances preserve their mechanical properties with increasing humidity until they dissolve at a substance-specific critical relative humidity of the surrounding air.…”
Section: Energy-dispersive X-ray Spectroscopymentioning
confidence: 99%
“…Differently, on amorphous water-soluble materials, water does not dissolve particles, but migrates into the amorphous molecular matrix, having a plastifying effect on the structure, with decrease of material viscosity and elasticity (Hartmann and Palzer 2011). Ronkart et al (2009a), evaluating commercial inulin dissolved in distilled water and spray-dried with air inlet temperature of 120 and 230°C, found that the formation of a continuous mass was observed for the initial amorphous samples stored at 75-94% relative humidity, when particles appeared fusedagglomerated. They also observed that the presence of crystals in the amorphous matrix limited the advanced caking of inulins.…”
Section: Energy-dispersive X-ray Spectroscopymentioning
confidence: 99%